Comparative Economic Impact of Green Energy Investments: Evidence from India, USA, Germany, and Denmark - Sathish Kumar Murugan; Prity Kumari; Teena Lakshmi Baskaran; Levente Dimen; Alina Cristina Nuta (Energies, 2025)
Renewable energy has become an imperative global focus in the battle against climate change, addressing energy security and the development of a sustainable energy economy. This study examines the economic effects of green energy investments in four distinct countries: India, the USA, Germany, and Denmark, using time-series data on employment generation, energy efficiency, and GDP growth for the period from 1996 to 2023. The study employed regression analysis, and the research isolates important differences in outcomes for these regions that are generated by renewable energy policies and investments. The findings suggest that labor-intensive renewable energy projects benefit emerging markets, such as India. Due to market saturation, the projects become counterproductive for mature markets like Germany. For large-scale project development in a stable policy environment, the USA scores highly, while Denmark excels in innovation and sustainability in wind energy. The study highlights the value of targeted policy interventions in maximizing the economic benefits from renewable energy. In addition, it emphasizes the need to tackle country-specific issues, encourage innovation, and ensure a fair pathway to a green energy system. The results of this research will be beneficial for policymakers and stakeholders in evaluating decisions regarding renewable energy investments.